AN EVALUATION OF PRESCRIPTION COMPLIANCE BASED ON THE FORMULARIUM IN OUTPATIENT PHARMACEUTICAL HOSPITAL ROYAL PRIMA MEDAN - Bagas Dwi Sanjaya; Jessica Vania Christine; Ermi Girsang; Sri Lestari Ramadhani Nasution (Sean Institute, 2023)
Evaluation of the hospital formulary must be carried out regularly and revised according to hospital policies and needs. The purpose of this research is toevaluatePrescribing adherence based on the formulary in the Outpatient Pharmacy of General Hospital (RSU) Royal Prima Medan. This researchis a mixed methods research. The population and sample used were patient prescription sheets for the period July 2022 - September 2022. The data obtained was analyzed using a retrospective descriptive method. The use of a drug is said to be in accordance with the formulary if it meets the percentage based on the 2008 minimum hospital service standard, namely 100%. The conclusion in this study is that adherence to drug prescriptions based on a formulary does not meet the minimum hospital service standard (100%) and needs to be evaluated to fulfill prescriptions based on a hospital formulary.